Comparison against 186 canid whole-genome sequences reveals survival strategies of an ancient clonally transmissible canine tumor - Decker, Brennan; Davis, Brian W.; Rimbault, Maud; Long, Adrienne H.; Karlins, Eric; Jagannathan, Vidhya; Reiman, Rebecca; Parker, Heidi G.; Drögemüller, Cord; Corneveaux, Jason J.; Chapman, Erica S.; Trent, Jeffery M.; et al. (Genome Research, 2015)
Canine transmissible venereal tumor (CTVT) is a parasitic cancer clone that has propagated for thousands of years via sexual transfer of malignant cells. Little is understood about the mechanisms that converted an ancient tumor into the world's oldest known continuously propagating somatic cell lineage. We created the largest existing catalog of canine genome-wide variation and compared it against two CTVT genome sequences, thereby separating alleles derived from the founder's genome from somatic mutations that must drive clonal transmissibility. We show that CTVT has undergone continuous adaptation to its transmissible allograft niche, with overlapping mutations at every step of immunosurveillance, particularly self-antigen presentation and apoptosis. We also identified chronologically early somatic mutations in oncogenesis- and immune-related genes that may represent key initiators of clonal transmissibility. Thus, we provide the first insights into the specific genomic aberrations that underlie CTVT's dogged perseverance in canids around the world.